2013
DOI: 10.1364/oe.21.010969
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum generation in As_2S_3-silica “nano-spike” step-index waveguide

Abstract: Efficient generation of a broad-band mid-infrared supercontinuum spectrum is reported in an arsenic trisulphide waveguide embedded in silica. A chalcogenide "nano-spike", designed to transform the incident light adiabatically into the fundamental mode of a 2-mm-long uniform section 1 µm in diameter, is used to achieve high launch efficiencies. The nano-spike is fully encapsulated in a fused silica cladding, protecting it from the environment. Nano-spikes provide a convenient means of launching light into sub-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…In recent years, several experimental and theoretical investigations on mid-infrared SC generation were reported in ChG planar waveguides [13][14][15], ChG fibers [16][17][18][19][20][21][22][23][24][25][26][27][28], single crystal sapphire fibers [29], silicon-on-insulator (SOI) wire waveguides [30], ZBLAN fiber [31], fluoride glass [32] and germano-silicate fibers [33]. Gai et al [13] reported SC generation from 2.9 µm to 4.2 µm in dispersion-engineered As 2 S 3 glass rib waveguide (6.6 cm long) pumped with 7.5 ps duration pulses at a wavelength of 3.26 µm with a pulse peak power of around 2 kW.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several experimental and theoretical investigations on mid-infrared SC generation were reported in ChG planar waveguides [13][14][15], ChG fibers [16][17][18][19][20][21][22][23][24][25][26][27][28], single crystal sapphire fibers [29], silicon-on-insulator (SOI) wire waveguides [30], ZBLAN fiber [31], fluoride glass [32] and germano-silicate fibers [33]. Gai et al [13] reported SC generation from 2.9 µm to 4.2 µm in dispersion-engineered As 2 S 3 glass rib waveguide (6.6 cm long) pumped with 7.5 ps duration pulses at a wavelength of 3.26 µm with a pulse peak power of around 2 kW.…”
Section: Introductionmentioning
confidence: 99%
“…The highly nonlinear waveguides used had hybrid As 2 S 3 -silica double-nanospike structures. They were fabricated using the pressure-assisted melt-filling technique, which enables a µm-diameter chalcogenide wire to be created inside a narrow silica capillary fiber [15,16]. The silica cladding provides a robust shield for the fragile chalcogenide microwire.…”
Section: Experimental Configurationmentioning
confidence: 99%
“…Free space coupling even with the highest numerical aperture objective lens is not efficient enough to couple light into subwavelength-sized silicon cores due to diffraction limited focusing and high Fresnel reflection at the silicon/air interface. Similar to the nano-tapers commonly used in planar silicon waveguides [18] and photonic crystal waveguides [19], inverse tapering of an As 2 S 3 (n = 2.4) core inside a silica clad fiber has been utilized to achieve free space optical coupling with a loss of 2 dB [20] and supercontinuum generation [21]. Direct splicing of silica-clad SCFs to conventional single mode fibers (SMFs) has also been demonstrated [9], and micro-structuring of the silicon core surface via chemical etching before splicing has been proposed to reduce Fresnel reflection [22].…”
Section: Introductionmentioning
confidence: 99%